New Pliocene hominin remains from the Leado Dido'a area of Woranso-Mille, Ethiopia. Issue 153 (April 2021) - Melillo, Stephanie M.; Gibert, Luis; Saylor, Beverly Z.; Deino, Alan; Alene, Mulugeta; Ryan, Timothy M.; Haile-Selassie, Yohannes
Abstract: Fossiliferous deposits at Woranso-Mille span the period when Australopithecus anamensis gave rise to Australopithecus afarensis (3.8–3.6 Ma) and encompass the core of the A. afarensis range (ca. 3.5–3.2 Ma). Within the latter period, fossils described to date include the intriguing but taxonomically unattributed Burtele foot, dentognathic fossils attributed to Australopithecus deyiremeda, and one specimen securely attributed to A. afarensis (the Nefuraytu mandible). These fossils suggest that at least one additional hominin lineage lived alongside A. afarensis in the Afar Depression. Here we describe a collection of hominin fossils from a new locality in the Leado Dido'a area of Woranso-Mille (LDD-VP-1). The strata in this area are correlated to the same chron as those in the Burtele area (C2An.3n; 3.59–3.33 Ma), and similar in age to the Maka Sands and the Basal through lower Sidi Hakoma Members of the Hadar Formation. We attribute all but one of the LDD hominin specimens to A. afarensis, based on diagnostic morphology of the mandible, maxilla, canines, and premolars. The LDD specimens generally fall within the range of variation previously documented for A. afarensis but increase the frequency of some rare morphological variants. However, one isolated M3 is extremely small, and its taxonomic affinity is currently unknown. The new observations support previous work on temporal trends in A. afarensis and demonstrate that the large range of variation accepted for this species is present even within a limited spatiotemporal range. The value added with this sample lies in its contribution to controlling for spatiotemporal differences among site samples in the A. afarensis hypodigm and its contemporaneity with non- A. afarensis specimens at Woranso-Mille.